A COST-EFFECTIVE ANALYSIS OF TIOTROPIUM WITH FORMOTEROL AND BUDESONIDE WITH FORMOTEROL BASED ON EFFICACY AND QUALITY OF LIFE IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS - Garnepudi, Kameswari; Shravanthi, Ivaturi; Sivakumar, Keerthana; Sharma M, Maithili; Manasa, Kurakula (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The primary objective of the study was to conduct the cost-effective analysis of tiotropium with formoterol versus budesonide with formoterol in the management of Stage-I chronic obstructive pulmonary disease (COPD) based on efficacy and quality of life (QoL). The study also aims to analyze the improvement of the QoL through pulmonary rehabilitation. The secondary objective was to evaluate the incidence of depression and anxiety in COPD patients. Methods: A prospective interventional study, with a sample size of 74 patients diagnosed with COPD Stage-I was conducted for 6 months. The study population was divided based on simple randomization into two main groups, one receiving tiotropium with formoterol and the other receiving budesonide with formoterol. Based on spirometry, their pulmonary function test (PFT) was recorded. The patients QoL was recorded using the WHOQoL-BREF questionnaire. Results: Data of 74 patients were collected for both the zero-degree and first-degree follow-up. The patients demonstrated good compliance with the transinhaler of the prescribed drugs. A significant improvement after providing pulmonary rehabilitation in PFT, i.e., forced expiratory volume1/ forced vital capacity values (p=0.000**) and the WHOQoL scoring (P = 0.001**) was observed in patients receiving tiotropium with formoterol. Tiotropium with formoterol was found to be more cost-effective treatment than budesonide with formoterol. Conclusion: The study showed that transinhalation of 9 mcg/12 mcg tiotropium/formoterol once a day is a better cost-effective treatment than 200 mcg/6 mcg transinhalation of budesonide/formoterol twice a day.